LEGAL REVIEW OF DIGITAL ASSET DEVELOPMENT IN INDONESIA - Erdina Louise Oudang (Jurnal Scientia, 2023)
Digital assets or often referred to as crypto assets is a new global phenomenon where the concept of digitization using blockchain technology and in the era of the industrial revolution 4.0, this phenomenon has begun to be understood by the public and in various countries, has been adopted and its legality is recognized. This technological development aims to provide accuracy, transparency and especially with a decentralized system that gives control to communities in society; while digital assets are tangible products within the blockchain system, with the aim of being a means of exchange, means of payment, means of storing data, means of investment, etc. The focus of the problems studied in this research is to review the law on the development of digital assets in Indonesia. The research method used in this research is a qualitative normative legal research method with a normative approach and the researchers process the data with qualitative data analysis. In legal practice and policy on digital asset regulation in Indonesia, crypto assets are a commodity investment tool that can be traded on the Futures Exchange; technical arrangements are regulated by the Commodity Futures Trading Regulatory Agency (Bappebti) under the Ministry of Trade, with CoFTRA Regulation Number 13 of 2022 concerning Amendments to CoFTRA Regulation Number 8 of 2021. The regulation regulates Guidelines for Organizing Crypto Asset Physical Market Trading in Futures Exchange. The issuance of this new regulation aims to strengthen the crypto and blockchain ecosystem in Indonesia, which continues to grow rapidly in Indonesia until this time the research was conducted.